The Influence of Joint Loading on Bone Marrow Lesions in the Knee: A Systematic Review With Meta-analysis. (December 2015) - Beckwée, David; Vaes, Peter; Shahabpour, Maryam; Muyldermans, Ronald; Rommers, Nikki; Bautmans, Ivan
Background: Bone marrow lesions (BMLs) are considered as predictors of pain, disability, and structural progression of knee osteoarthritis. The relationship between knee loading and BMLs is not yet completely understood. Purpose: To summarize the available evidence regarding the relationship between joint loading and the prevalence and progression of BMLs in the tibiofemoral joint. Study Design: Meta-analysis. Methods: Three databases (PubMed, Web of Science, and The Cochrane Library) were systematically screened for studies encompassing BMLs and changes in knee loading. A methodological quality assessment was conducted, and a meta-analysis computing overall odds ratios (ORs) was performed where possible. Results: A total of 29 studies involving 7641 participants were included. Mechanical loading was categorized as body weight and composition, compartmental load, structural lesion, and physical activity. High compartmental loads and structural lesions increased the risk for BMLs (overall ORs ranging from 1.56 [95% CI, 1.13-2.15] to 8.2 [95% CI, 4.4-15.1]; P = .006). Body weight increased the risk for BMLs to a lesser extent (overall OR, 1.03; 95% CI, 1.01-1.05; P = .007). Contradictory results for the effect of physical activity on BMLs were found. Conclusion: Augmented compartmental loads and structural lesions increased the risk of the presence or progression of BMLs. Body weight increased the risk for BMLs to a lesser extent. Contradictory results for the effect of physical activity on BMLs may be explained by a dose-response relationship, knee alignment, and structural lesions. Clinical Relevance: It has been shown that unloading the knee temporarily may induce beneficial effects on osteoarthritis-related structural changes. Therefore, an early recognition of BMLs in the aging athlete's knee may provide information to counter the onset and aggravation of symptomatic knee osteoarthritis by reducing the knee load.